The Impact of Sustainable Marketing Strategies and Career Development Opportunities on Employee Productivity and Customer Loyalty in Jakarta - Noor Aziz; Asa Sheila Amelia; Fauzi Ichwani; Gumoyo Munpuni Ningsih; Aula Nurul Ma'rifah (Westscience Press, 2026)
In an increasingly competitive business environment, organizations are required to implement strategies that not only enhance organizational performance but also promote long-term sustainability and customer retention. This study aims to examine the impact of Sustainable Marketing Strategies and Career Development Opportunities on Employee Productivity and Customer Loyalty in Jakarta. A quantitative research approach was employed using a survey method involving 200 respondents working in various organizations across Jakarta. Data were collected through structured questionnaires measured using a five-point Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results indicate that Sustainable Marketing Strategies have a positive and significant effect on Employee Productivity (β = 0.382, p < 0.001) and Customer Loyalty (β = 0.291, p < 0.001). Career Development Opportunities also significantly influence Employee Productivity (β = 0.467, p < 0.001) and Customer Loyalty (β = 0.177, p = 0.010). Furthermore, Employee Productivity exerts the strongest direct effect on Customer Loyalty (β = 0.431, p < 0.001). The structural model explains 65.3% of the variance in Employee Productivity and 71.2% of the variance in Customer Loyalty, indicating substantial predictive capability. The findings suggest that organizations should integrate sustainability-oriented marketing initiatives with employee development programs to enhance workforce productivity and strengthen long-term customer loyalty. This study contributes to the literature by providing an integrated framework that combines external sustainability strategies and internal human resource development practices within a single model.